The valuable characteristics of oats genotypes and resistance to Fusarium disease - I. G. Loskutov; E. V. Blinova; O. P. Gavrilova; T. Yu. Gagkaeva (Вавиловский журнал генетики и селекции, 2016)
A comprehensive field- and laboratory-based assessment of the eco-geographical and intraspecific diversity of oats helps determine the parameters, on the basis of which it is possible to select genotypes that may serve as genetic sources for breeding. The study aims to analyze the relationship of agronomic traits of oat genotypes from the VIR collection with resistance to Fusarium disease. The agronomic characters and disease resistance of 340 genotypes of hulled and naked oats belonging to the cultivated species Avena sativa L., A. byzantina C. Koch, A. abyssinica Hoch. and A. strigosa Schreb. of different geographical origin have been tested in field and laboratory conditions in 2007–2009 and in 2014. The artificial infection with Fusarium sporotrichioides Sherb. was used to evaluate bacterial loads and mycotoxin contamination in the oat genotypes. An integral analysis has shown that the duration of the second half of the vegetation period, resistance to lodging and pathogen infection, plant height and panicle elongation facilitate grain infection. It has been found that A. strigosa and A. sativa are less susceptible to Fusarium than A. byzantina and A. abyssinica. Naked oats are more resistant to Fusarium disease if compared to the hulled ones. A comparison of evaluation results for the local and bred genotypes has shown that local accessions with the unilateral panicle and dark-colored floral glumes are more resistant to Fusarium disease. When considering the geographical origin, a higher degree of resistance was discovered in local varieties from China as well as in some accessions from Russia and USA and bred cultivars from Belarus. In total, the characters studied made it possible to identify oat genotypes with high yield and resistance to Fusarium disease.